Application of the hazard identification risk assessment and risk control method in the welding frame body process (a case study in indonesian company) - Qamarani, Awanis Shabrina; Vikaliana, Resista (LPPMPK - Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2024)
PT X is an Indonesian manufacturing industry company that manufactures, assembles and distributes motorcycles, which was established in 1971. PT X uses machinery and heavy equipment in its production process, and accidents can occur during the process. Therefore, this study aims to identify potential hazards, analyze the level of risk and risk control and provide recommendations for control measures that can be applied by PT X, especially in the welding frame body process. By using the Hazard Identification Risk Assessment and Risk Control (HIRARC) method. The results of this study indicate that there are 19 potential hazards and 19 risks, where the level of risk in the extreme category is 2, the high category is 6, the medium category is 8, and the low category is 3. Based on the risk control implemented by PT X, it can reduce the level extreme category risk from 2 to 0, high category from 6 to 0, medium category from 8 to 5, and increases the level of low risk category from 3 to 14. Risk control recommendations that can be implemented by PT X in order to reduce the level of risk is by replacing cotton gloves to leather gloves, using a double mask, changing welding goggles to a welding mask, and using a leather apron.